Back to school - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Looking for possibilities for a MSc or a PhD degree in agricultural development? A scholarship with the International Institute for Tropical Agriculture (IITA) may be the answer. Successful candidates conduct research in line with IITA s agenda and...